Arterial Stiffness and Left Ventricular Diastolic Function in Subjects with Euthyroidism - Yang, Lijuan; Sun, Xiuqin; Tao, Hong; Zhao, Yi (Reviews in cardiovascular medicine, 2022)
Objective: Previous literature has suggested that the cardiovascular risk factors associated with subclinical hypothyroidism (SCH) may be found in subjects with euthyroidism, but research relating to increased arterial stiffness (AS) and left ventricular (LV) diastolic dysfunction, which have been proven to exist in patients with SCH, is limited in patients with euthyroidism. The aim of this study was to investigate this. Methods: A total of 249 participants with euthyroidism were divided into two groups based on their thyroid-stimulating hormone (TSH) levels: Group A (TSH level ranging from 0.49 to 2.5 mIU/L, n = 170) and Group B (TSH level ranging from 2.5 to 4.91 mIU/L, n = 79). The Cardiovascular Profiling System through brachial-ankle pulse wave velocity (baPWV) was used to assess AS, and the LV function was evaluated using Color-Doppler-Echocardiography. The Student’s unpaired t-test and Pearson’s χ2 test were conducted to compare the clinical parameters. Spearman’s correlation analysis and multiple logistic regression analysis were used to analyze the association between thyroid function, baPWV, and LV diastolic function parameters. Results: Significant differences existed between the two groups in free triiodothyronine (fT3) values and systolic blood pressure (BP) (p < 0.05). When compared with Group A, the baPWV was higher, the A wave increased, and the E/A ratio was lower in Group B (p < 0.01). The multiple logistic regression analysis showed that fT3 was associated with a higher baPWV (p < 0.001). The E/A ratio was directly correlated with TSH, fT3, and baPWV (p < 0.05), and diastolic BP was significantly directly correlated with the E/A ratio (p < 0.05). Thyroperoxidase antibody was not a significant variable in the regression analysis (p > 0.05). Conclusions: An association was found between thyroid function, baPWV, and the E/A ratio in subjects with euthyroidism. Further study is needed to confirm these conclusions.